Vibration monitoring and acoustic emission sensing during progressive load tests of corroded reinforced concrete beams - van de Velde, Menno; Vandecruys, Eline; Verstrynge, Els; Reynders, Edwin; Lombaert, Geert (Engineering structures, 2024)
Corrosion of reinforcement in concrete civil structures poses a significant challenge to their integrity and durability. To ensure the safety and longevity of such structures, effective monitoring strategies that can accurately detect, localise and assess the progression of damage are crucial. For most existing concrete structures, this is often challenging, as damage is already present when the monitoring campaign starts. In addition, reinforced concrete structures can be subject to a combination (or a succession) of corrosion and load-induced damage. By combining multiple measurement techniques, a more accurate and reliable condition assessment of concrete civil structures can be aimed for. This paper presents a comprehensive experimental study of the combination of vibration-based monitoring (VBM) and acoustic emission (AE) sensing techniques during progressive load tests of corroded reinforced concrete beams. Five beams were subjected to a cyclic four-point bending test, three of which were previously corroded while two beams remained undamaged prior to the mechanical loading. The influence of pre-existing corrosion damage and corresponding longitudinal concrete cracking on the modal characteristics (natural frequencies and strain mode shapes) and AE outcomes is investigated during the four-point bending test. The monitoring results obtained by both techniques are shown to be influenced by the pre-existing longitudinal concrete cracking caused by the reinforcement corrosion. Lower AE activity and a lower reduction in natural frequencies is observed for corroded RC beams during load bending tests when compared to uncorroded specimens. In addition, bending cracks occurring within the corroded zones appear to have a very limited effect on the identified strain mode shapes. These observations could possibly result in an underestimation of the damage and corresponding overestimation of the load-carrying capacity, as the corrosion damage conceals the occurrence of bending cracking on the AE and VBM outcomes. •Combined approach of AE and VBM is employed to assess mechanical damage in previously corroded RC beams.•AE signals during load testing and during reinforcement corrosion are compared.•Pre-existing corrosion damage shows a significant influence on the AE and VBM outcomes.•AE localisation and strain mode shapes can detect and localise early concrete cracking.